PENDUGAAN MODEL PERAMALAN VOLUME IMPOR PAKAN TERNAK - Herlena Bidi Astuti; Wawan Eka Putra; Emlan Fauzi; Yesmawati Yesmawati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Feed is an important element in developing livestock business. At present, imports are still needed to meet domestic needs. This study aims to examine the best forecasting model for the volume of animal feed imports. The data used are monthly import volume data from 2015: 1-2019: 9 used for this study and three models namely Moving Average, exponential smoothing and simple linear regression. the selection of the best model is based on the value of MAPE, MAD and MSD or MSE. The results showed that the best forecasting model was the Simple Linear Regression method.